New Method of 2-Substituted Benzothiazole Synthesis from 2-Aminothiophenol Derivatives and Acetophenone - Nguyen, Le Anh; Doan, Hong Van; Ngo, Quoc Anh (JST: Engineering And Technology For Sustainable Development, 2021)
Benzothiazole is one of the compounds with many interesting biological activities. The synthetic methods previously studied have been carried out under complex conditions such as under strong acidic environment, high temperature or expensive catalysts and undergo many reaction steps. In this study, we report a new method of synthesizing benzothiazole in a reaction step under no solvent, no metal catalysts, using low-cost starting materials. The ability to participate in the reaction of various 2-aminothiophenol derivatives has been investigated and the product has obtained a fairly to excellent performance. We have successfully synthesized seven derivatives of benzothiazole with good yield under mild conditions.